Development of a novel MALDI-TOF MS-based bile solubility test for rapid discrimination of Streptococcus pneumoniae - Evgeny A. Idelevich; Andreas Schlattmann; Markus Kostrzewa; Karsten Becker (Elsevier, 2020)
Differentiation of Streptococcus pneumoniae from other Streptococcus mitis group streptococci (SMGS) remains challenging despite the introduction of matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS). While the bile solubility test (BST) provides most reliable discrimination of pneumococci, its practical implementation is limited by subjective visual interpretation and frequent inconclusive results. We aimed to develop a rapid confirmation BST based on direct-on-target MALDI-TOF MS assay. After establishment of optimal test conditions, test performance was evaluated on 36 consecutive clinical SMGS isolates. Colony material was suspended and pipetted onto a MALDI target. After drying, sodium deoxycholate in different concentrations (2%, 5%, and 10 %) was added. Incubation for 30 min (at room temperature or 35 °C) was followed by liquid removal and spot washing. After adding 70 % formic acid, spots were overlaid with matrix and measured (MALDI Biotyper smart, Bruker). The absence of microbial spectra (Biotyper score <1.7) in samples with sodium deoxycholate indicated efficient removal of bacterial biomass due to bile solubility, thus, identifying pneumococci. In contrast, scores ≥1.7 were interpreted as lack of bile solubility and confirmation as viridans streptococci other than S. pneumoniae. Highest test accuracy was achieved applying 5% sodium deoxycholate at 35 °C and 10 % sodium deoxycholate at room temperature. These test conditions provided 100 % sensitivity and 100 % specificity for discrimination of S. pneumoniae. The developed MALDI-TOF MS-based BST is an easy-to-perform assay with minimum hands-on time and objective readout. The promising results of this proof-of-principle study warrant confirmation with large collections of epidemiologically diverse strains.